Effect of nitrogen on growth, productivity and seed quality of long grain rice (Research in Agriculture Livestock and Fisheries, 2019)
Field experiment was conducted at the experimental farm of Bangabandhu Sheikh Mujibur Rahman Agricultural University, Gazipur during Aman season to optimize nitrogen requirement of long grain rice (var. BUdhan 1) in respect to high yield and seed quality. Seven levels of nitrogen fertilizer viz. 0, 20, 40, 60, 80,100 and 120 kg N ha-1 constituted the treatment variables. Application of nitrogen fertilizer significantly influenced morphological event of the variety where days required for expressing phenological events increased with the increase of nitrogen levels. Growth parameters like plant height (114.37 cm), tillers per hill (15.1) and dry matter accumulation were pronounced at higher level of nitrogen. However, plants with moderate level (60 kg ha-1) of applied nitrogen showed better yield component of the variety where the highest number of panicle per hill (11.8), grains per panicle (140.5) filled grains per panicle (130.33) and bolder seed size were recorded with 60 kg N ha-1. Better yield components of the variety obtained at 60 kg N ha-1 attributed to highest yield (4.43). Considering seed quality, seeds obtained from 60 kg N ha-1showed significantly higher viability, germination and vigor indices. Therefore, it is desirable to collect seeds of BUdhan 1 with moderate level of nitrogen to ensure higher yield with better seed quality of BUdhan 1.Res. Agric., Livest. Fish.6(2): 279-287, August 2019